Guillain-Barre syndrome 15 days after COVID-19 despite SARS-CoV-2 vaccination. (2021) - Finsterer, Josef
Abstract: Guillain-Barre syndrome (GBS) following a SARS-CoV-2 vaccination has been repeatedly observed but GBS following a SARS-CoV-2 infection in a vaccinated patient has not been reported. A 69yo female developed paresthesias of both lower and upper limbs which were followed by progressive muscle weakness. The history was positive for a mild SARS-CoV-2 infection 15 days earlier. COVID-19 occurred despite a first dose of a vector-based SARS-CoV-2 vaccine, 40 days prior to onset of GBS. Since CSF investigations and nerve conduction studies were indicative of GBS, subtype acute, inflammatory, demyelinating polyneuropathy (AIDP), immunoglobulins (30 g/d) were started. After two weeks complete recovery was achieved. In conclusion, SARS-CoV-2 infections may develop despite full vaccination and may be complicated by GBS. Since no other trigger of GBS could be identified, a causal relation between the SARS-CoV-2 infection and GBS was suspected.